2014
DOI: 10.1124/jpet.114.217802
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Receptors and the Persistent Neurovascular Dysregulation Induced by Methamphetamine Self-Administration in Rats

Abstract: Recently abstinent methamphetamine (Meth) abusers showed neurovascular dysregulation within the striatum. The factors that contribute to this dysregulation and the persistence of these effects are unclear. The current study addressed these knowledge gaps. First, we evaluated the brains of rats with a history of Meth selfadministration following various periods of forced abstinence. Micro-computed tomography revealed a marked reduction in vessel diameter and vascular volume uniquely within the striatum between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
0
5
0
4
Order By: Relevance
“…However, different studies have reported that METH, MDMA, and MDPV all induce similar effects on the vasculature [41-45]. For instance, in association with NO signaling [17] METH induces cerebral blood vessel vasoconstriction [42] and a reduction in cerebral blood flow [43] . MDMA induces coronary [45] and peripheral [46] vasoconstriction, whereas MDPV also induces peripheral [41] and integumentary vasoconstriction, as well as an increase in brain temperature, effects that suggest vasoconstriction of cerebral blood vessels [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, different studies have reported that METH, MDMA, and MDPV all induce similar effects on the vasculature [41-45]. For instance, in association with NO signaling [17] METH induces cerebral blood vessel vasoconstriction [42] and a reduction in cerebral blood flow [43] . MDMA induces coronary [45] and peripheral [46] vasoconstriction, whereas MDPV also induces peripheral [41] and integumentary vasoconstriction, as well as an increase in brain temperature, effects that suggest vasoconstriction of cerebral blood vessels [44].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the less severe stress exposure employed in the current study could explain why stress did not alter Meth self-administration. Additionally, the absence of stress induced potentiation of Meth self-administration could be due to the unrestricted access to Meth that was allowed in this study compared to other studies where the duration of access to the drug is limited each day 34 , 35 . The lack of drug availability during the time the animal is not in the operant chamber could trigger withdrawal-associated processes that promote craving and increase drug administration in the stressed group 36 .…”
Section: Discussionmentioning
confidence: 95%
“…Dopaminergic neurons cause vasomotor changes in brain microvasculature [74]. In METH users, dopamine receptor activation largely accounts for cerebral vasoconstriction [75], with a marked reduction in regional blood flow in the insular cortex [76,77]. A decrease in striatal and cortical perfusion is maintained in abstinent users [57,78].…”
Section: Perfusion Damagementioning
confidence: 99%